Design and development of Google glass-based campus navigation system - Ang, Kevin James C. (Animo Repository, 2018)
This paper investigates the feasibility of a Google Glass-based campus navigation system for both indoor and outdoor areas. The Indoor Positioning System (IPS) of the proposed system utilizes the magnetic positioning technology of IndoorAtlas Maps™ API which depends on structure's magnetic field fluctuations or geomagnetic fingerprints. The outdoor navigation mechanism simply consists of a map displayed within the Google Glass app with an augmented routing path leading to the set destination, while the indoor navigation interface displays a blue dot indicator of the current position on top of the augmented map with minimum spanning tree route. Furthermore, a data logging feature is incorporated for logging the movements of the user through the use of QR coded checkpoints for outdoor location monitoring and indoor-to-outdoor navigation transitions. The proposed system was tested in De La Salle University (DLSU) - Manila Campus, where 30 participants (15 DLSU and 15 Non-DLSU) were invited to utilize the proposed system navigating from an entry point to a set destination. The proposed Google Glass-based navigation system was found to have an average error of 1.77 meters (indoor) and around 77% of the users who utilized the application responded with a positive feedback. However, Google glass’ limited battery life and high cost are among the barriers to adaptation. These results could provide empirical evidence supporting the feasibility of Google glass-based navigation deployment in other public areas, e.g. malls, government buildings, hospitals, etc. © 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.